Manufacturing process improvement and mechanical modelling of multiwalled carbon nanotube/epoxy composites. (June 2013) - Kim, M; Okoli, O I; Jack, D; Park, Y-B
Abstract : Multiwalled carbon nanotube (MWNT) reinforced epoxy resin composites were fabricated and characterised. Several process variables were investigated using design of experiments. The MWNTs (0·5 wt-%) were dispersed in Epon 862 epoxy resin under various sonication conditions. Young's modulus, energy to failure, glass transition temperature T g and storage modulus E ′ were assessed. The first three were selected in a design of experiment optimisation study. The results indicated that as the sonication intensity and the duration of sonication were increased, the material response of the MWNT/epoxy composite, specifically Young's modulus, energy and T g, was enhanced. The fracture surfaces of the composites were examined using scanning electron microscopy. Improved dispersion was observed in samples fabricated with increased sonication intensities. The Mori–Tanaka model was used to predict the mechanical properties of the MWNT/epoxy composites and was found to be in reasonable agreement with experimental data. Nonetheless, the experimental results yielded slightly inferior properties to those from the model prediction.